ARTIFICAL INTELLIGENCE IN ENGLISH-MEDIATED COMMUNICATION: BIBLIOMETRIC ANALYSIS OF EMERGING RESEARCH PATTERN (2000-2024) - Laksani, Hening; Muslihah, Isnawati (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
The rapid integration of Artificial Intelligence (AI) into communication practices has transformed the interaction processes by means of bridging language barriers, assisting communication from different languages and cultures. This research aims to map the research trend on AI within English-mediated communication by exploring publication patters, collaboration networks, and thematic scopes in Scopus-indexed journal. Bibliometric analysis was used to interpret thematic transition retrieved from Scopus database period 2000-2024 in order to visualize the co-occurrences and co-citation networks within the field. The findings revealed the remarkable improvement in research about the role of AI in communication processes over the past decade. It revealed significant contributing regions of having highest attention in this scope including US and China, with the leading institution was Stanford University. Meanwhile, the co-citation mapping recognized the authors in this area such as Hancock and Zhai. The findings revealed the role of AI in English-mediated communication covered a wide range of interdisciplinary paradigm integrating several subject areas.